The Influence of Transaction Complexity, Audit Budget, and Auditor Turnover on Misstatement Detection - Tampubolon, Ricky Bryan D.P. (Universitas Pendidikan Nasional, 2025)
This study investigated the influence of transaction complexity, audit budget, and auditor turnover on the detection of material misstatements in financial statement audits. Using a quantitative approach with a survey design, data were collected from 158 external auditors working in public accounting firms in Jakarta. Respondents were selected through purposive sampling, requiring at least two years of professional auditing experience. The research instrument was distributed both in-person and online, and all responses were deemed valid for analysis. The results of multiple regression analysis showed that transaction complexity had a negative and significant effect on misstatement detection, indicating that higher transaction complexity reduced auditors’ effectiveness in identifying errors or fraud. Auditor turnover also demonstrated a negative and significant effect, suggesting that frequent changes in audit personnel decreased the continuity of knowledge and reduced the ability to detect misstatements. Conversely, audit budget did not have a significant effect, implying that the allocation of audit resources and time did not directly determine detection effectiveness. Simultaneous testing revealed that transaction complexity, audit budget, and auditor turnover collectively affected misstatement detection, with an explanatory power of 80.5%. These findings highlighted the importance of considering multiple risk factors in audit planning, particularly the challenges posed by complex transactions and frequent personnel turnover. The study contributed to the understanding of audit quality determinants in Indonesia and provided practical implications for audit firms in managing resources and maintaining team stability to enhance misstatement detection.